Analysis of drying kinetics of eggplant through thin layer models and evaluation of texture and colour properties - Ferrão, Ana Cristina (2019)
Eggplant is a food with unique characteristics. However, due to its high moisture content it is very perishable. Thus, to increase its shelf life it can be applied the drying process. This work aimed at studying the effects of drying on eggplant, namely on the physical properties of colour and texture, as well as the analysis of drying kinetics by thin layer models. The drying was carried out using a convection chamber with a temperature of 80ºC and an air velocity of 0.5 m/s. The texture profile analysis was done with a texturometer equipped with a 75 mm probe and the colour measurement was performed with a calorimeter in the CIELab coordinates. For both texture and colour, all analysis were done in triplicate, before and after drying. The results showed that there were clear differences in colour, with the difference being higher in the case of the dried sample (E = 25.95) when compared to the fresh sample analysed 10 minutes after the cut (E = 9.69).Regarding the texture, drying caused alterations in the eggplant structure, with an increase in elasticity and chewiness and a decrease in hardness, resilience and cohesiveness. As for the kinetics, the sample took 2.5 hours to reach a moisture content of approximately 10%. Four thin layer models were tested, being the Wang & Singh model the one that proved to be the most suitable to fit the experimental data, with a correlation coefficient equal to 0.9902.